DETERMINAN KINERJA PENGELOLAAN KEUANGAN DESA DENGAN KOMITMEN ORGANISASI SEBAGAI PEMODERASI (STUDI PADA KANTOR DESA DI KECAMATAN SERUWAY) - hidayana, hidayana; Afrah Junita; Iqlima Azhar (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2024)
This research aims to determine the influence of apparatus competency, transparency and accountability on village financial management performance with organizational commitment as a moderating variable. This type of research uses quantitative research, the data source for this research uses primary data. The population and sample of this research are villages in Seruway sub-district, totaling 15 villages as a population and the samples taken in this research were 60 village financial managers who were chosen randomly. This research uses purposive sampling, namely a certain sampling technique based on a consideration or some criteria. The data obtained was analyzed using SPSS (Statistical Package For Social Sciences) analysis techniques. The equation model analyzed is multiple linear regression analysis and Moderated Regression Analysis (MRA), classical assumption testing and hypothesis testing (T test, F test and Determination Coefficient (R2)). The results obtained from this research are:apparatus competency has a significant effect on village financial management performance,organizational commitment moderates apparatus competency on village financial management performance, (3) transparency has a significant effect on village financial management performance,Organizational commitment moderates transparency in village financial management performance,accountability has a significant effect on village financial management performance,organizational commitment moderates accountability in village financial management performance. The limitations of this research are that many village officials do not have adequate educational background and do not have good competence in managing finances and also lack experience. Given these limitations, the author can provide suggestions, namely that future researchers are expected to be able to develop and perfect further research in the future. Village officials in Seruway District as village financial managers should increase their knowledge, skills and training regarding the preparation of good and correct financial reports so that financial management performance can run well.